What visualising strategic reading means for young adolescents. Issue 4 (2nd October 2019) - Reyes, Cynthia C.; Bishop, Penny A.
Abstract: Since middle school is a critical time for literacy learning in general and comprehension in particular, educators are left to ponder how best to teach these students. In addition, what role might student perception of reading strategies through visual depictions have in order to help teachers decide how best to guide their students with challenging reading. In this conceptual piece, questions that guided our research were, What can we learn from students about the strategies they use to read challenging texts? and How do these strategies challenge adult norms of what constitutes strategic reading for young adolescents? We collected and analysed 332 seventh grade student drawings that depicted how students approached difficult text, identifying types of reading strategies. We used Mokhtari and Reichard's framework of Support, Problem-Solving and Global reading strategies as a holistic and analytic lens to group the codes where appropriate. Findings revealed students' heavy reliance on support and problem-solving strategies, in contrast to relatively few global strategies, suggesting a need for educators to teach global strategies skills more often and directly. Unexpected findings further revealed a visually powerful alternative response, which suggest that educators should consider how to manage more affective reactions to challenging text.